PENYUSUNAN PROGRAM TAHUNAN,PROGRAM SEMESTER, DAN KRITERIA KETUNTASAN TUJUAN PEMBELAJARAN - Juspita Sari Pita; Andi Reskiya Syafira; Agus Setiawan; Takdirmin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the development of mathematics learning programs covering the preparation of Annual Programs (Prota), Semester Programs (Prosem), and Criteria for Achievement of Learning Objectives (KKTP) within the Merdeka Curriculum framework. Using a conceptual literature review method, this article systematically analyzes educational regulations and relevant academic literature. The findings reveal that Prota serves as a general one-year learning guide, Prosem as a detailed semester-level operational plan, and KKTP as an interval-based evaluation instrument replacing the conventional minimum mastery criterion (KKM). These three components are interdependent and must be prepared collaboratively by considering the Learning Outcomes (CP), academic calendar, and student characteristics. Proper implementation enhances teaching quality and supports the character and learning independence of students in line with the spirit of the Merdeka Curriculum.